The high frequency of healthcare use in patients one year prior to a sarcoidosis diagnosis - Gerke, Alicia K; Tang, Fan; Pendergast, Jane; Cavanaugh, Joseph E; Polgreen, Philip M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: The clinical presentation of sarcoidosis can be varied. Prior investigations have shown that diagnosis is often delayed over six months, particularly in patients with pulmonary symptoms. Delays may lead to high healthcare use prior to diagnosis.  Objective: To investigate healthcare use prior to diagnosis of sarcoidosis for a cohort of insured patients. Methods: We conducted a case-control study using a de-identified limited dataset of private health insurance claims.  Cases were identified as persons with sarcoidosis from 2003-2009. Controls with other respiratory-related diagnoses (asthma, chronic obstructive pulmonary disease, pneumonia) were matched by age, gender, and diagnosis date. We compared frequencies of doctor visits, prescriptions, and imaging in the year prior to established diagnosis. Results: We identified 206 cases and 2060 controls and compared healthcare use patterns in the year prior to diagnosis. Among those receiving prescriptions, a larger proportion of cases received two or more antibiotic courses (69% vs. 55%, p=0.0020) or two or more corticosteroid prescriptions (63% vs. 50%, p=0.0137). On average, cases had more doctor visits (14.7 vs. 7.8, p